The Development and Usability of a Bragg’s Law Crystallography Model as a Teaching Aid in Solid State Physics Course among Undergraduate Students in Universiti Pendidikan Sultan Idris - Yeong Yi Wong; Faridah Lisa Supian (PILLAR OF PHYSICS EDUCATION, 2021)
This quantitative study was aimed to develop and determine the usability of a Bragg’s law crystallography model as a teaching aid in Solid State Physics course among undergraduate students in Universiti Pendidikan Sultan Idris (UPSI). The usability of Bragg’s law crystallography model in attracting students’ interest towards the learning area and the perception of students towards the usability were evaluated. A total of 101 UPSI undergraduate students were taken as the respondents in the study via the cluster probability sampling method. A questionnaire with four points Likert scale was used to collect the data. The instruments including the model and the questionnaire were verified by evaluation experts. Pilot test was carried out to measure the reliability of instruments. The data was analysed by using the descriptive statistics. The findings showed that the developed Bragg’s law crystallography model was valid and reliable for undergraduate students in UPSI. Positive result of the students’ interest towards the learning area by using the Bragg’s law crystallography model and the usefulness of this model was showed. Students showed great interest during the lecture learning about Bragg’s law. Thus, Bragg’s law crystallography model enabled students to be more interested in the learning area and helped the educators to create better learning environment in Solid State Physics course as the implications of this research